Cross-species comparison of aCGH data from mouse and human BRCA1- and BRCA2-mutated breast cancers - Holstege, Henne; van Beers, Erik; Velds, Arno; Liu, Xiaoling; Joosse, Simon A; Klarenbeek, Sjoerd; Schut, Eva; Kerkhoven, Ron; Klijn, Christiaan N; Wessels, Lodewyk FA; Nederlof, Petra M; Jonkers, Jos (BMC cancer, 2010)
Background Genomic gains and losses are a result of genomic instability in many types of cancers. BRCA1 - and BRCA2 -mutated breast cancers are associated with increased amounts of chromosomal aberrations, presumably due their functions in genome repair. Some of these genomic aberrations may harbor genes whose absence or overexpression may give rise to cellular growth advantage. So far, it has not been easy to identify the driver genes underlying gains and losses. A powerful approach to identify these driver genes could be a cross-species comparison of array comparative genomic hybridization (aCGH) data from cognate mouse and human tumors. Orthologous regions of mouse and human tumors that are commonly gained or lost might represent essential genomic regions selected for gain or loss during tumor development. Methods To identify genomic regions that are associated with BRCA1 - and BRCA2 -mutated breast cancers we compared aCGH data from 130 mouse Brca1 Δ/Δ ;p53 Δ/Δ , Brca2 Δ/Δ ;p53 Δ/Δ and p53 Δ/Δ mammary tumor groups with 103 human BRCA1- mutated, BRCA2- mutated and non-hereditary breast cancers. Results Our genome-wide cross-species analysis yielded a complete collection of loci and genes that are commonly gained or lost in mouse and human breast cancer. Principal common CNAs were the well known MYC -associated gain and RB1/INTS6 -associated loss that occurred in all mouse and human tumor groups, and the AURKA -associated gain occurred in BRCA2-related tumors from both species. However, there were also important differences between tumor profiles of both species, such as the prominent gain on chromosome 10 in mouse Brca2 Δ/Δ ;p53 Δ/Δ tumors and the PIK3CA associated 3q gain in human BRCA1- mutated tumors, which occurred in tumors from one species but not in tumors from the other species. This disparity in recurrent aberrations in mouse and human tumors might be due to differences in tumor cell type or genomic organization between both species. Conclusions The selection of the oncogenome during mouse and human breast tumor development is markedly different, apart from the MYC gain and RB1-associated loss. These differences should be kept in mind when using mouse models for preclinical studies.